A PRAGMATIC STUDY: ILLOCUTIONARY ACTS IN "YOWES BEN 2" MOVIE - Arnoi, Khoirun Nisaa'; Muhamad Safi'i; Arif Alexander Bastian (Aisyah Journal of English Language Teaching (AIJELT), 2024)
This study explores speech acts as pragmatic studies in the film "Yowes Ben 2". The researcher will investigate the many forms of speech acts and classify them focusing on the illocutionary categories employed in the film. This study follows John Rogers Searle's (1975) illocutionary action theory, which is assertive (the speaker's confidence in something), directive (something the listener should do), commissive (commitment to do something), expressive (expression of an attitude or feeling), and declarative (making changes such as pointing, stating, etc.)The research design implemented in this study is qualitative. Researchers gathered information by screening the film "Yowes Ben 2" and analyzing the different forms of speaking acts. Researchers employed content analysis to analyze their data. The steps in data analysis are as follows: the researcher will identify, analyze, interpret, and draw conclusions. In accordance to the data, expressive speech acts account for the greatest number of illocutionary acts (56%). Directive speech accounted for 38%, commissive speech 3%, representational speech 0%, and declarative speech 3%.